Comparing drying characteristics of melantai, keledang, kekatong, and khaya timbers using three different drying methods - Rabidin, Zairul Amin (2012)
A study was undertaken to determine and compare drying characteristics of melantai (Shorea spp.), keledang (Artocarpus spp.), kekatong (Cynometra spp.) and khaya (khaya grandifoliola) representing light hardwood, medium hardwood, heavy hardwood, and plantation timbers dried using air drying, kiln drying and radio frequency/vacuum drying systems. The specific objectives of these studies were; firstly, to determine physical properties of timbers related to drying, i.e. moisture content, density, and shrinkage; secondly, to compare characteristics of 30 mm thick, end-matched lumbers dried by these three different drying methods; and thirdly, to evaluate effect of thickness (30 and 55 mm thick), degree of vacuum and temperature settings, mode of heating (continuous and intermittent) and surface quality (planed/unplaned) on drying time and quality of RFV dried timber. Drying characteristics of the timbers were compared at final moisture content (MC), i.e. 15-18% MC for air drying and 12% MC for kiln- and RFV-drying, in terms of drying time, drying rate, formation of defects, shrinkage, moisture distribution between and within the lumbers, and drying stresses. Moisture content of keledang in green condition was relatively higher than khaya, followed by melantai and kekatong. The highest density and shrinkage in all directions were observed in kekatong. Density of keledang was higher than melantai and khaya but the shrinkage values for these three timber species were not too different. RFV drying reduces the drying time compared with kiln drying. The percentage of reduction in drying time for 30 mm thick lumbers were about 56.3% for melantai, 19.4% for keledang, and 47.4% for kekatong. Generally, air dried timber for 30 mm thick lumbers posses more uniform moisture content between lumbers than those RFV- and kiln-dried. However, moisture gradient in 55 mm thick lumbers was relatively higher than 30 mm thick. The variation of moisture content between and within lumbers for RFV dried timber was lower than that of kiln dried. Within lumbers, RFV dried timber had lower inner-outer moisture content difference than that of kiln dried lumbers. A number of lumbers dried by RFV had a drier inner compared to the outer layer. In RFV drying, the moisture content of the lumbers increased from the centre towards the bottom and top of the stack. The quality of melantai, keledang and khaya dried by air drying, kiln drying and RFV drying were comparable. The quality of kekatong lumbers dried by RFV was comparable to air dried and relatively better than kiln dried. Shrinkage of the timber dried by RFV was almost similar to air drying, but lower than kiln drying. Ratio of tangential to radial shrinkage and volumetric shrinkage for RFV dried was relatively lower than kiln dried lumbers. No casehardening was observed on all species dried by air drying. Casehardening is lower in RFV dried timber as compared to kiln drying. RFV drying times increased with increasing thickness. The percentage of increment in drying time for dense timber was relatively higher than less dense timber. Moisture content variation within lumber for 30 mm and 55 thick lumbers were within the acceptable limit of ±2%. Planing timber before RFV drying not only facilitate timber stacking but also reduced the drying time and moisture content variation between and within lumbers. Drying time for lumbers dried under intermittent mode of heating was higher than countinuous mode. In general, melantai, keledang and khaya can be dried succesfully under continuous mode of heating with temperature and pressure set at 40o C and 40 torr respectively. Slower drying settings, i.e. drying under intermittent mode of heating and at 50 torr vacuum pressure should be used when drying kekatong.